PROSEDUR PENYITAAN BARANG BUKTI TINDAK PIDANA PENGGELAPAN OLEH PENYIDIK KEPOLISIAN SEKTOR KELAPA LIMA SERTA KENDALA-KENDALA DALAM PROSES PENYITAAN SEBAGAI TOLAK UKUR TINGKAT KEPERCAYAAN MASYARAKAT KEPADA INSTITUSI POLRI - Nalle, Nyongky D; Tallo, Daud D; Fallo, Debi F. Ng. (Petitum Law Journal, 2025)
The crime of embezzlement of motor vehicles that occurs in Kupang City is influenced by several factors in general, one of which is economic factors. For example, in a case with the number: LP/217/X/2022/Sektor Kelapa Lima. Based on the results of the investigation, the evidence was successfully identified, but there was no follow-up in the form of forcibly taking evidence from the possession of the dealer to be secured by the Kelapa Lima sector police on the grounds that they had not obtained a permit to confiscate evidence from the Court. However, after obtaining a permit from the Court, the Kelapa Lima sector police did not confiscate evidence on the grounds of lack of personnel. Article 38 of the Criminal Procedure Code has expressly stated that confiscation can only be carried out by investigators with a permit from the chairman of the local court. It should have been carried out with a permit from the chairman of the confiscation court. The application of a rule of law is one of the systems that must be carried out to realize a legal goal itself, namely achieving justice, utility, and legal certainty. Legal certainty can be applied in the confiscation of evidence in a criminal act.